P36 Development of the STADPLAN intervention on advance care planning in care dependent community-dwelling older persons in germany. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Kirchner, Ä; Langner, H; Meyer, G; Schnakenberg, R; Silies, K; Chuvarayan, Y; Hoffmann, F; Köpke, S; Köberlein-Neu, J; Berg, A
Abstract : Background: The STADPLAN project is a multicentre, cluster-randomised controlled trial on advance care planning (ACP) in older people receiving professional home care. The aim of the intervention is to encourage patients to deal with the topic of ACP in a structured way, to nominate a surrogate decision maker and to regularly discuss own preferences and wishes with this person. Methods: Following the MRC framework for complex interventions, we systematically adapted the intervention components of existing ACP programmes to the needs of community nursing care in Germany. The design of the modelled multicomponent intervention was guided by the Behaviour Change Wheel method. Experts reviewed and discussed the proposed intervention programme. Results: The complex intervention addresses patients aged ≥ 65 years, nursing professionals and general practitioners comprising: A minimum of two guideline–based conversations led by qualified nurses to be offered to dyads of patients and relatives. A two–day training course including practical exercises to prepare nurses for the conversations. Written information about ACP provided to patients, aiming to encourage patients to reflect on and write down own wishes and health care preferences in various situations. The information offers further local counselling options for the preparation of ACP documents. Participants' general practitioners will receive concise written information about the study. Conclusion: The acceptance, feasibility, and comprehensibility of the complex intervention are currently piloted in four home care services including 120 patients. Results are expected in early 2019 and will be used to optimise the intervention before the efficacy trial.